The Small Firm - Set at the Start - Birley, Sue (Cranfield School of Management, 1985)
The research studied extent to which the employment size of the new firm is set at the start, how many subsequently grow, and whether those which survive AND grow have any identifiable characteristics.
To be presented at the Sixth Annual Babson Entrepreneurship Research Conference 1986